Application of FTIR spectroscopy and multivariate calibration for determination of Acid Orange 7 and Sudan II in blusher products - Novalina B. R. Purba&, Abdul Rohman, Sudibyo Martono (Journal of Applied Pharmaceutical Science, 2019)
The aim of this study was to optimize Fourier transform infrared (FTIR) spectroscopy and multivariate calibration for the quantitative analysis of Acid orange 7 (AO-7) and Sudan II (S-II) in blusher products. The calibration and validation samples were made by adding known concentrations of AO-7 and S-II in the placebo of blusher cosmetics products. High-performance liquid chromatography equipped with photodiode array detector at 300–650 nm was used to determine the actual values of AO-7 and S-II. The separation of AO-7 and S-II was performed using C18 column at 40oC with mobile phase of acetonitrile-water in gradient elution program. FTIR spectra of evaluated samples were scanned using FTIR spectrophotometer equipped with attenuated total reflectance (ATR) sampling technique. The correlation between actual values of AO-7 and S-II as determined using high-performance liquid chromatography and FTIR predicted values was facilitated with multivariate calibrations. The selection of calibration models relied on highest r2 and lowest levels of root mean square error of calibration, root mean square error of prediction, and root mean square error of cross validation. The optimization results showed that FTIR spectra-partial least square regression (PLSR) using wavenumbers of 3,450–2,400 cm−1 and six factors offered the highest r2 value (r2 > 0.98) and lowest errors. FTIR with ATR technique could be used to predict AO-7 and S-II in blusher product with the main advantage of its simplicity, rapidity, and minimum sample preparation.
Keywords: Acid orange 7, Sudan II, HPLC, FTIR multivariate, PLSR, PCR, Blusher.